An Analysis of Figurative Language Used on Political Discussion at Prime Time News Metro TV - Nur Afifah; Andi Muhammad Irawan (English Language and Literature, 2023)
This study describes about how figurative language used in several political discussions which are presented in Prime Time News Metro TV YouTube Channel. This study was not only described types of figurative language but also described each meaning/message. The source of data based on four selected videos which had similar theme called The Upcoming 2024’s Election in Indonesia, those were appeared between January to April 2022. In data analysis, it found that there were 204 utterances containing of figurative language. Therefore, based on Keraf(2009) classifications there were 7 types of figurative language found in this study which are simile, metaphor, personification, synecdoche, irony, sarcasm and innuendo. In this results, metaphor became the most frequent type of figurative language. Moreover, this study also found 5 types of meaning among 7 types of meaning in Pardede(2016) namely; conceptual meaning, connotative meaning, social meaning, affective meaning and reflected meaning. In shorts, there were three results of this study: firstly, connotative meaning became the most frequent type of meaning, secondly, it was compatible to the general assumption about figurative language was rich of imply meaning; lastly, metaphor had special role to emphasize the speaker’s intention while using other figurative language like sarcasm and innuendo.